Analisis Manajemen Risiko pada UMKM “Seblak Raos di Jawa Tengah” - Amalia, Tanti; Nurhandayani, Dini; Rahma fadzillah, Kylla Almira (Jurnal Serambi Ekonomi dan Bisnis, 2024)
Risk management analysis is an important aspect in maintaining the sustainability of micro, small, and medium enterprises (MSMEs). This study aims to analyze risk management in MSME Seblak Raos, a culinary business that is growing amidst competition in the snack food business. A qualitative approach is used with in-depth interview methods and direct observation to identify operational, financial, and marketing risks. The results of the study indicate that the main risks faced by MSME Seblak Raos include fluctuations in raw material prices, dependence on certain suppliers, changes in consumer preferences, and price competition. To manage these risks, this MSME has implemented a product diversification strategy, built good relationships with suppliers, and increased promotion through social media. This study recommends strengthening the financial recording system and risk management training for business owners. With good risk management, MSME Seblak Raos can increase its competitiveness and business sustainability.